Application of Deep Breathing Relaxation Therapy on the Violent Behavior of Patients with Schizophrenia - Firman Maulana; Menik Kustriyani; Heny Prasetyorini (International Journal Of Health Science, 2026)
Schizophrenia is a chronic mental disorder that triggers maladaptive emotional responses, such as violent behavior, which can endanger the patients themselves, others, or the environment. Deep breathing relaxation therapy serves as a non-pharmacological management that stimulates the parasympathetic nervous system, lowers stress hormones, and enhances anger control capabilities. To determine the effect of deep breathing relaxation therapy on violent behavior in patients with schizophrenia. This study utilized a one-group pre-test and post-test approach. The deep breathing relaxation therapy was implemented for 7 consecutive days with a duration of 15 minutes per day for 4 male respondents with violent behavior at RSJD Dr. Amino Gondohutomo. The instruments used were the Standard Operating Procedure (SOP) for deep breathing relaxation therapy along with a violent behavior observation questionnaire. This study has been declared ethically cleared under letter number 000.9/1347/II/2026. Prior to the intervention (pre-test), the respondents’ average self-control capability score was 50% (poor). Following the intervention (post-test), the score increased to 82% (good). The patients became calmer, less irritable, and their aggressive impulses were reduced. The application of deep breathing relaxation therapy is effective and has a significant influence on enhancing self-control and reducing violent behavior in schizophrenic patients.